Association of oxidative damage measured by 8-hydroxyguanosine formation with altered risks to hepatocellular carcinoma in Malaysian study population - Ahmad, Zalinah; Makpol, Suzana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Oxidative damage is an important factor contributing to ageing and many degenerative diseases. It can be detected by the DNA base damage, which is formation of 8-oxo-7,8-dihydro-2’deoxyguanosine (8-oxodG). The 8-oxodG is an important indicator of oxidative stress and has been competently specified as a recognized initiator of the carcinogenic process and premutagenic injury in mammalian cells. Aims: In this preliminary study, we investigated the possible association of oxidative DNA damage in hepatocellular carcinoma (HCC) patients in comparison with Malaysian healthy controls taking into account the different races and genders in both groups. Method: DNA of peripheral white blood cells was isolated from 91 HCC patients and 304 controls. The level of oxidative DNA damage was determined by ELISA procedure. Results: Quantitative measurement of 8-oxodG was higher in HCC patients at mean value of 3.30 ± 2.32 ng/ml. In controls, the average value is 1.57 ± 1.92 ng/ml. Comparison between gender showed that there was a significant difference observed in the level of 8-oxodG between male and female in controls, where p = 0.003. The level of 8-oxodG was higher in male than in female controls. There was a significant difference in the average value of 8-oxodG level between the controls and HCC patients where p<0.001. However, no significant difference in the level of 8-oxodG value was observed when compared between Malays and the non-Malays. Conclusion: HCC patients showed greater oxidative damage to DNA as compared to controls and this suggests oxidative DNA damage may contribute to the pathogenesis of HCC.